Hits against microbial bacteroicin the product by bacteria Lactobacillus salivarius toward the negative bacterial species to dye gram - Mohamed, Eman Hamza; AL-Yasseen, Ahlam K.N. (Al-Qadisiyah Journal of Pure Science, 2017)
collected 155 samples from various clinical sources included 20 samples of vaginal swabs, 8 saliva swabs, 6 sample milk of lactating mothers for the period of October -2012 until March -2013. The results of the isolation and laboratory diagnosis and biochemical tests the ownership of 34 isolated bacteria Lactobacillus salivarius and the highest percentage isolate bacterial (33.3)% of the samples of the vagina. All isolates showed bacteria Lactobacillus salivarius effectiveness of the microbial against toward some negative bacterial species to dye grams diameters ranged between inhibition zones (8-2) cm, as results showed portability 4 isolates selected to produce bacteriocin. The results showed that the Rf bacteriocin values produced by the bacterium Lactobacillus salivarius isolates ranged from (5.4 to 2.3) for deposit bacteriocin and between (6-4.3) for leaky bacteriocin, The Leaky bacteriocin was more effective in the inhibition compared with deposit bacteriocin.